2012
DOI: 10.1371/journal.pone.0038322
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of the Human PNPLA3 Gene Are Strongly Associated with Severity of Non-Alcoholic Fatty Liver Disease in Japanese

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) includes a broad range of liver pathologies from simple steatosis to cirrhosis and fibrosis, in which a subtype accompanying hepatocyte degeneration and fibrosis is classified as nonalcoholic steatohepatitis (NASH). NASH accounts for approximately 10–30% of NAFLD and causes a higher frequency of liver-related death, and its progression of NASH has been considered to be complex involving multiple genetic factors interacting with the environment and lifestyle.Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
206
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(227 citation statements)
references
References 24 publications
16
206
2
3
Order By: Relevance
“…Relatively lower levels of TRIB1 expression due to the minor allele of rs6982502 might have resulted in increased levels of plasma lipid and progression to hepatic steatosis. While TRIB1 has not been significantly associated with NAFLD diagnosed by computed tomography (CT) (Romeo et al 2008, Kawaguchi et al 2012, the GWAS of plasma AST levels in Europe found a significant association with the SNP, rs2954021, which localized in the same LD block as rs17321515 (Chambers et al 2011). A weak association between rs2954021 and hepatic steatosis was also identified (Chambers et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively lower levels of TRIB1 expression due to the minor allele of rs6982502 might have resulted in increased levels of plasma lipid and progression to hepatic steatosis. While TRIB1 has not been significantly associated with NAFLD diagnosed by computed tomography (CT) (Romeo et al 2008, Kawaguchi et al 2012, the GWAS of plasma AST levels in Europe found a significant association with the SNP, rs2954021, which localized in the same LD block as rs17321515 (Chambers et al 2011). A weak association between rs2954021 and hepatic steatosis was also identified (Chambers et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Familial clustering and ethnic differences in susceptibility indicate that genetic factors may be important risk determinants for development and progression of NAFLD/ NASH [32][33][34][35][36]. Variation in the enzyme adiponutrin (patatin-like phospholipase domain-containing protein 3; PNPLA3) is a major genetic determinant of hepatic steatosis and fibrosis [33][34][35].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Variation in the enzyme adiponutrin (patatin-like phospholipase domain-containing protein 3; PNPLA3) is a major genetic determinant of hepatic steatosis and fibrosis [33][34][35].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Polymorphisms of PNPLA3 gene have been found to be strongly associated with the pathogenic status of NAFLD in different populations [91][92][93] . PNPLA3 gene, encoding adiponutrin is known to have lipase activity in vitro and has been found to be involved in glucose and lipid metabolism [91] .…”
Section: Genes That Affect Lipolysismentioning
confidence: 99%